(untitled) (Bangladesh Medical Journal, 2019)
Gradual rising of crime among adolescents is now a social and public health concern worldwide. A total of 1.9 million children getting incarcerated worldwide yearly where in Bangladesh, 1.3 million of children engaged in hazardous job most of them involved in crime. Again, physical and mental well-being is the legal and constitutional rights of the every adolescent including detained adolescent of Juvenile Development Centers. This is a cross-sectional study conducted to assess the physical and mental health status as well as socio-demographic status of adolescents of two Government Juvenile Development Center, Tongi and Konabari, Gazipur from January to December 2017. 191 adolescents were selected purposively (male: female=1.41:1). Data were collected by face to face interview and record review and height and weight of the respondents were measured. The mental health status was measured by WHO-5 Well-being Scale. The age range was from 13 to 17 years. Age of the respondents were significantly correlated with score of the WHO-5 well-being scale (p=0.028). The study observed higher score among respondents who had detained here for more than 2 months which was highly significant (p<0.001). Most of the respondents (75.9%) belong to poor family. The mean score of the WHO-5 well-being scale of the respondent was 52.20±10.0, where 35.1% had good and 64.9% had poor psychological well-being status and higher among male respondents (52.92±10.40) than the female respondents (51.29±9.45). The respondents who were employee prior to this institution had significantly high score (p=0.024). A significant relationship was observed between type of crime and the score of WHO-5 well-being scale (p=0.003). The mean body mass index was 20.26±1.27 kg/m2. Almost every respondent (92.7%) belongs to normal nutritional category. Well-being score of the respondents was significantly increased with the body mass index (p=0.005). This study revealed score of WHO-5 well-being scale was significantly associated with duration of stay of the respondents (p<0.001, R=0.540). Thus this study provides prevalence of mental health status and nutritional status as well as socio-demographic condition of adolescents of Government Juvenile Development Centre in Bangladesh which may provide the Government, sociologists and psychologists valid and reliable data for making plans and policies for improving or updating the living conditions of detainee of Juvenile development Centre. Bangladesh Med J. 2018 May; 47 (2): 7-11